2021
DOI: 10.3390/s21113829
|View full text |Cite
|
Sign up to set email alerts
|

Infection-Mediated Clinical Biomarkers for a COVID-19 Electrical Biosensing Platform

Abstract: The race towards the development of user-friendly, portable, fast-detection, and low-cost devices for healthcare systems has become the focus of effective screening efforts since the pandemic attack in December 2019, which is known as the coronavirus disease 2019 (COVID-19) pandemic. Currently existing techniques such as RT-PCR, antigen–antibody-based detection, and CT scans are prompt solutions for diagnosing infected patients. However, the limitations of currently available indicators have enticed researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 110 publications
(156 reference statements)
0
5
0
Order By: Relevance
“…A fundamental aspect of managing this pandemic effectively revolves around having strong and swift diagnostic tools [1], [2]. Nevertheless, their drawbacks related to accessibility, speed, and sensitivity have emphasized the pressing requirement for alternative diagnostic approaches [3]. As a response to these challenges, researchers have undertaken a mission to create advanced diagnostic technologies that combine affordability, portability, rapid detection, and ease of use, making them suitable for widespread adoption within healthcare systems [3], [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fundamental aspect of managing this pandemic effectively revolves around having strong and swift diagnostic tools [1], [2]. Nevertheless, their drawbacks related to accessibility, speed, and sensitivity have emphasized the pressing requirement for alternative diagnostic approaches [3]. As a response to these challenges, researchers have undertaken a mission to create advanced diagnostic technologies that combine affordability, portability, rapid detection, and ease of use, making them suitable for widespread adoption within healthcare systems [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, their drawbacks related to accessibility, speed, and sensitivity have emphasized the pressing requirement for alternative diagnostic approaches [3]. As a response to these challenges, researchers have undertaken a mission to create advanced diagnostic technologies that combine affordability, portability, rapid detection, and ease of use, making them suitable for widespread adoption within healthcare systems [3], [4]. This effort aligns with the changing landscape of medical research, where fields like biotechnology and electronics are converging to develop state-of-the-art solutions [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most reported methods are based on either fluorescence or colorimetric detection, reducing the accuracy and selectivity compared to conventional reverse transcriptase-polymerase chain reactions (RT-PCR) [ 8 , 12 , 16 , 31 ]. However, sensitivity of the LAMP method can be enhanced by analyzing the electrical properties after the amplification process, thereby increasing the accuracy, minimizing the use of samples, and reducing the total procedure time [ 32 ]. In a typical configuration, electrochemical DNA sensors use a single-stranded capture probe sequence immobilized on a working electrode, where the complementary target DNA is hybridized.…”
Section: Introductionmentioning
confidence: 99%
“…Most techniques rely on the decrease in current response of a free-to-diffuse intercalating redox reporter during the reaction processes [ 39 , 40 ]. Some studies have also reported the use of field-effect transistor devices for the detection of SARS-CoV-2; however, this approach has a drawback of high noise signals [ 32 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioelectronic devices or biosensors are becoming increasingly important in the medical field. Moreover, bioelectronic devices or biosensors are used to detect diseases and monitor medical information [1][2][3][4][5][6][7][8]. Among the important medical factors, body temperature is the most important indicator of health problems and is often used for early detection of health problems.…”
Section: Introductionmentioning
confidence: 99%